2022
DOI: 10.3390/s22134973
|View full text |Cite
|
Sign up to set email alerts
|

Balance and Posture in Children and Adolescents: A Cross-Sectional Study

Abstract: Balance and posture are two topics that have been extensively studied, although with some conflicting findings. Therefore, the aim of this work is to analyze the relationship between the postural angles of the spine in the sagittal plane and the stable static balance. A cross-sectional study was conducted with children and adolescents from schools in northern Portugal in 2019. An online questionnaire was used to characterize the sample and analyze back pain. Spinal postural angle assessment (pelvic, lumbar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
3
0
6
Order By: Relevance
“…It has been demonstrated that excessive screen use can have a negative impact on students' physical and mental health. For example, it has been linked to neck and back pain (Azevedo et al, 2023), obesity (Fang et al, 2019, Khajeheian et al, 2018, Zhang et al, 2016, sleep disturbances (Parent et al, 2016), and depressive symptoms (Hoare et al, 2016, Suchert et al, 2015. Furthermore, there is a risk of distraction from social media, which has the potential to affect learning.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that excessive screen use can have a negative impact on students' physical and mental health. For example, it has been linked to neck and back pain (Azevedo et al, 2023), obesity (Fang et al, 2019, Khajeheian et al, 2018, Zhang et al, 2016, sleep disturbances (Parent et al, 2016), and depressive symptoms (Hoare et al, 2016, Suchert et al, 2015. Furthermore, there is a risk of distraction from social media, which has the potential to affect learning.…”
Section: Discussionmentioning
confidence: 99%
“…Digital learning environments also require long periods spent in front of screens (Ilchenko et al, 2022). These advantages and disadvantages of block scheduling should be redefined for ODE, especially those relating to the health aspect (Azevedo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [8] indicated muscle fatigue after poor shoulder and cervical posture and speculates on its effects on possible pathologies. One objective of the study of Azevedo et al [9] was to investigate whether postural angles and stable static balance parameters are related to the manifestation of back pain. Through their analysis, they found a statistically significance between the postural angle of the thoracic spine and the manifestation of back pain in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%